2022
DOI: 10.3390/app12105134
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Fly Ash Self-Hardened Adsorbent Monoliths for Methylene Blue Removal from Aqueous Solutions

Abstract: The use of methylene blue (MB) by several industries generates contaminated industrial wastewaters that must be purified before discharge into the environment. Its removal can be achieved by adsorption, and low-cost and easily available materials should be used as adsorbents. Biomass fly ash (BFA) generated from biomass combustion, for heat and power generation, is increasing worldwide since the process is considered CO2 neutral. However, most of the ash is still landfilled. This study aims to evaluate the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…The XRD pattern of the BFA samples shows that α-quartz (α-SiO 2 ), calcite (CaCO 3 ), microcline (KAlSi 3 O 8 ), and muscovite (KAl 2 (AlSi 3 O 10 )(OH) 2 ) are the main crystalline detected phases. These findings are in line with the results obtained in XRF and with the crystalline phases reported in the literature (quartz and calcite) [ 4 , 13 , 14 , 15 ]. When qualitatively comparing the BFA1 and BFA2 diffractograms with those of the sieved fractions (BFA1_S and BFA2_S), it is possible to observe that the peaks referring to α-quartz decrease in intensity.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The XRD pattern of the BFA samples shows that α-quartz (α-SiO 2 ), calcite (CaCO 3 ), microcline (KAlSi 3 O 8 ), and muscovite (KAl 2 (AlSi 3 O 10 )(OH) 2 ) are the main crystalline detected phases. These findings are in line with the results obtained in XRF and with the crystalline phases reported in the literature (quartz and calcite) [ 4 , 13 , 14 , 15 ]. When qualitatively comparing the BFA1 and BFA2 diffractograms with those of the sieved fractions (BFA1_S and BFA2_S), it is possible to observe that the peaks referring to α-quartz decrease in intensity.…”
Section: Resultssupporting
confidence: 92%
“…Their surface is generally rough and not strongly vitreous. These morphology features fit the descriptions made by other authors [ 4 , 15 , 16 , 17 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The prepared monoliths were positively tested for MB adsorption. It was shown that the dye adsorption kinetics can be described by the pseudo-first-order equation and the adsorption process was characterised by the Type 2 Langmuir isotherm model with a maximum sorption capacity of ~0.66 mg/g, determined for the samples with the higher total porosity, ~72% (Capela et al, 2022).…”
Section: Dyesmentioning
confidence: 99%